Design and development of lightweight concrete incorporating expanded polystyrene beads - Tey, Lee Huan, 1989-; A. S. M. Abdul Awal, supervisor; Fakulti Kejuruteraan Awam (2014)
Thesis (Sarjana Kejuruteraan (Awam - Struktur))) - Universiti Teknologi Malaysia, 2014